A Novel Germline TP53 Mutation in a Patient With Li-Fraumeni Syndrome: Resolving a Variant of Uncertain Significance. Issue 8 (25th November 2021) - Douglass, David P.; Stine, Kimo C.; Farrar, Jason E.
Abstract : Increasing availability of genomic testing poses new challenges to clinicians, particularly where variant interpretation from commercial sources may be equivocal. The authors report a patient with recurrent rhabdomyosarcoma and subsequent bilateral breast cancer who was found to harbor a previously undescribed germline TP53 sequence alteration annotated by the commercial laboratory as a variant of uncertain significance. By investigating publicly available databases of aggregated normal germline and malignant somatic genomic sequences, the authors conclude that this missense variant, c.476C>T (p.A159V), is a novel, pathogenic Li-Fraumeni syndrome mutation and demonstrate the utility of these resources in clinical pediatric hematology and oncology practice.